Role of territorial speckle tracking echocardiography in identifying the localization of significant coronary artery disease in patients with non-ST-segment elevation acute coronary syndromes. (14th October 2021) - Gherbesi, E; Chiarello, G; Paiocchi, V L; Leo, L A; Schlossbauer, S A; Faletra, F F
Abstract: Background: In non-ST-segment elevation acute coronary syndromes (NSTE-ACS) patients, several studies demonstrated that 2D speckle tracking echocardiography (STE) is able to predict the presence of coronary artery disease (CAD). Conversely, the role of STE for the localization of significant CAD is less well established. Purpose: To investigate the role of territorial longitudinal (TLS) and circumferential strain (TCS) assessed with STE as a non-invasive predictor of localization of significant CAD in patients with NSTE-ACS. Methods: We retrospectively enrolled NSTE-ACS patients with significant stenosis (≥70%) at least in one major epicardial coronary artery and without previous cardiovascular events over two years of time. Echocardiography was recorded before coronary angiography and myocardial strain was evaluated offline by an operator blinded to clinical data. Territorial strain was calculated grouping and averaging the strain values of the segments perfused by the 3 major coronary arteries. Results: 150 patients were included (age 66.3±11.8 years, 71% male; 90.7% NSTEMI and 9.3% unstable angina). ROC curve analysis demonstrated the ability of TLS and TCS to identify the presence of coronary stenosis of LAD, LCX or RCA (AUC for TLS-LAD 0.74 [0.66–0.82] p=0.0001; LCX 0.73 [0.65–0.81] p=0.0001; RCA 0.69 [0.60–0.77] p=0.0001-AUC for TCS-LAD 0.80 [0.70–0.90] p=0.0001; LCX 0.76 [0.67–0.85] p=0.0001; RCA 0.65 [0.55–0.75] p=0.0001), superior to territorial wall motion score index (Figure 1). The diagnostic value was confirmed in the subgroup of patients without wall motion abnormalities for TLS and for TCS, except for RCA. Conclusion: Territorial strain assessed with STE might be a non-invasive tool to localize coronary artery stenosis in patients with NSTE-ACS, even without wall motion abnormalities. Funding Acknowledgement: Type of funding sources: None.